2010
DOI: 10.1037/a0018118
|View full text |Cite
|
Sign up to set email alerts
|

The jumping to conclusions bias in delusions: Specificity and changeability.

Abstract: There are indications that a jumping to conclusions bias (JTC) plays a role in the formation and maintenance of delusions and should be targeted in therapy. However, it is unclear whether (a) JTC is uniquely associated with delusions or simply an epiphenomenon of schizophrenia or impaired intellectual functioning and (b) it can be changed by varying task demands, motivational factors, or feedback. Seventy-one patients with schizophrenia spectrum disorders and either acute or remitted delusions and 68 healthy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(81 citation statements)
references
References 46 publications
4
76
0
1
Order By: Relevance
“…Moreover, as proposed by Freeman (2007), anxiety might have a stronger role in delusion maintenance where the purpose of the delusional belief could be to lower the anxiety levels in patients. Interestingly, induced anxiety states are associated with enhanced JTC bias and with paranoid ideation in healthy people (Lincoln et al, 2010a(Lincoln et al, , 2010b. In healthy participants, this relationship between delusional ideas and anxiety might be dependent of the environmental condition and be triggered in specific situations only.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Moreover, as proposed by Freeman (2007), anxiety might have a stronger role in delusion maintenance where the purpose of the delusional belief could be to lower the anxiety levels in patients. Interestingly, induced anxiety states are associated with enhanced JTC bias and with paranoid ideation in healthy people (Lincoln et al, 2010a(Lincoln et al, , 2010b. In healthy participants, this relationship between delusional ideas and anxiety might be dependent of the environmental condition and be triggered in specific situations only.…”
Section: Discussionmentioning
confidence: 94%
“…However, it appears likely that the increased JTC was observed because of the increased paranoia. In healthy people, some found that inducing anxiety significantly increases the JTC bias and the levels of state paranoia in high scorers on the CAPE, a psychotic experiences questionnaire (Lincoln et al, 2010a(Lincoln et al, , 2010b) whilst others did not find effect of induced anxiety on the JTC bias (Keefe and Warman, 2011). Given the lack of strong rationale behind an association between JTC and depression or anxiety, we hypothesise that delusions are independently related to JTC and emotions.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…The notion of bias or style in cognitive processing refers to both formal and social reasoning partiality and includes a propensity to make decisions based on inadequate data, a resistance to disconfirmatory information, and 'self-serving' attributions in social situations. For example, the most often cited effect originates from the observation that schizophrenia patients with persecutory delusions are inclined to 'jump to conclusions' and make impulsive and premature decisions exclusive of sufficient information on probabilistic reasoning tasks (Dudley et al, 2015;Lincoln, Ziegler, Mehl, & Rief, 2010;Garety et al, 1991;Garety et al, 2005;So, Garety, Peters, & Kapur, 2010). Delusional patients also tend to rigidly hold their beliefs and refuse to consider any disconfirmatory evidence (Woodward, Moritz, Cuttler, & Whitman, 2006).…”
Section: Study Aimmentioning
confidence: 99%